2017
DOI: 10.1186/s13256-017-1304-5
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib found to cause eyelash growth: a case report

Abstract: BackgroundHypereosinophilic syndrome is a hematologic disorder in which the eosinophils proliferate.Oral Janus kinase inhibitors are known to be effective treating hypereosinophilic syndrome. Janus kinase inhibitors have also demonstrated efficacy in alopecia. Madarosis is a condition in which the eyelashes are missing or absent and can been seen in alopecia patients.Case presentationWe present the case of a 77-year-old Asian man who was diagnosed with hypereosinophilic syndrome, refractive to all medications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Previous reports tried to highlight the effect of other medications on hair growth, in a study of Song et al,24 they reported a case of unexpected eyelash growth much longer than they were normally, under the effect of ruxolitinib treatment. Also, in a study of Riahi et al,25 they reported excellent and sustained growth of eyebrows with continual daily use of bimatoprost 0.03% solution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports tried to highlight the effect of other medications on hair growth, in a study of Song et al,24 they reported a case of unexpected eyelash growth much longer than they were normally, under the effect of ruxolitinib treatment. Also, in a study of Riahi et al,25 they reported excellent and sustained growth of eyebrows with continual daily use of bimatoprost 0.03% solution.…”
Section: Discussionmentioning
confidence: 99%
“… 64 Eyelash growth was observed in a patient with hypereosinophilic syndrome after having taken ruxolitinib, but the responsible mechanism was not elucidated. 67 …”
Section: Ruxolitinibmentioning
confidence: 99%
“…They empirically showed the historic infection data of some known botnet that uses the same infection type with more than 80% accuracy. Jungsuk et al [69] showed cross analysis among 10 spamming botnet to analyze malware infected host. the external parameter.…”
Section: Irc Based Analysismentioning
confidence: 99%